The impact of the interval between the last meal and the onset of farrowing on the duration of farrowing, stillbirth rates, and colostrum production in highly productive sows in a tropical climate - AKKHAPHANA, Tip-Apa; NGANSUCHARIT, Kritchaya; SRISURACH, Srisuda; TAECHAMAETEEKUL, Preechaphon; ADI, Yosua Kristian; TUMMARUK, Padet (Journal of Veterinary Medical Science, 2024)
The present study investigated impact of the interval between the last meal and the onset of farrowing on the duration of farrowing, stillbirth rates, and colostrum production in highly productive sows in a tropical climate. The study involved a total of 92 Danish Landrace x Yorkshire sows (herd A) and 114 French Landrace × Yorkshire sows (herd B). In herd B, a total of 61 sows had their blood samples collected within 1 hr after the onset of farrowing to evaluate their blood glucose levels. The interval between the last meal and the onset of farrowing averaged 5.9 ± 4.5 and 5.4 ± 4.1 hr in herds A and B, respectively. Neither the duration of farrowing nor the occurrence of stillborn piglets in both herds was affected by the time gap between the last meal and the onset of farrowing. At the onset of farrowing, the average blood glucose level in sows was 77.1 ± 19.3 mg/dL, with a range of 27 to 115 mg/dL. There was a positive correlation observed between the blood glucose concentration and the colostrum yield of the sows (r=0.261, P=0.042). In conclusion, the time interval between the last meal and the onset of farrowing did not have any impact on the farrowing performance of sows. However, a higher concentration of blood glucose at the onset of farrowing was associated with an improvement in the colostrum yield of the sows.